Comparison of ram, wether and ewe market lamb slaughter and carcass characteristics - Kropf, Donald H.; Menzies, C.S.; Harrison, D.L.; Anderson, L. (Kansas Agricultural Experiment Station, 2011)
Lambs used were sired by Hampshire rams the first two years; by Hampshire, Suffolk, Southdown, Dorset, and Rambouillet rams the third year. All lambs were from western ewes and were individually slaughtered as they reached 95 lbs. Carcasses were graded and chilled carcass weights were obtained after a 48-hour chill. Fat thickness measurements were taken over the loin eye muscle at the ¼, ½, and ¾ points and loin eye cross-sectional area was determined.
Keywords: Ram; Wether; Ewe; Carcass characteristics